The Impact of Team Dynamics on Software Quality and Productivity: Evidence from South Africa - Tshipuke Vhahangwele; Bassey Isong; Adnan Abu Mahfouz (Journal of Information System and Informatics, 2026)
Software quality and productivity are influenced not only by technical practices but also by the social dynamics within development teams. This study investigates the combined effect of team dynamics, including trust, communication, collaboration, diversity, and conflict resolution, and software development practices on project outcomes. A mixed-methods design combined regression, Spearman’s Rho, and thematic analysis of survey data from 124 South African software professionals. The findings indicate that trust is the strongest positive predictor of software quality and productivity, while communication effectiveness and the use of collaboration tools also improve software outcomes. Equally, unstructured collaboration, excessive planning meetings, and poorly managed communication channels negatively affect performance. Diversity and effective conflict resolution were positively associated with productivity and efficiency. Thematic analysis corroborated these findings, illustrating how unclear communication, low trust, and dysfunctional collaboration lead to delays, rework, and lower quality. The study confirms that successful software outcomes emerge from the alignment of social and technical subsystems, highlighting the critical role of team dynamics in realising the full potential of software development practices. It contributes empirical evidence from an understudied developing-country context and proposes a socio-technical framework to enhance software quality and productivity.